Dactylorhiza elata, Stately Dactylorhiza - Vela, E.V. (2019)
Mediterranean regional assessment: Near Threatened (NT) The species is found from southwestern Europe and northwestern Africa. In two countries within the Mediterranean distribution (France and Portugal) populations or habitat of this species have declined by more than 30% over three generations. In another two countries (Algeria and Morocco) a similar decline is suspected but cannot yet be confirmed, and in Spain populations appear to be relatively abundant however there is no information on population trends. Elsewhere the species is known only from singlesites in Sardinia and Tunisia. whilst the extent of occurrence is very large, the area of occupancy (AOO) is possibly restricted however distribution data are inadequate to confirm the AOO. Therefore whilst the rate of decline cannot be measured throughout the range of the species, the Mediterranean population decline is confirmed, it is ongoing and is not reversible, consequently this species is close to classification as Vulnerable (A2c and A4c). Further to this, if monitoring data become available to provide an indication of population trends in Spain and these show that it is in decline then it is clear that the species should be considered threatened at both the Mediterranean and global scales. This species is therefore classed as Near Threatened, approaching Vulnerable (A2c+4c).